Bacterial Profiles and Antibiotic Resistance in Chronic Obstructive Pulmonary Disease Patients with Exacerbation and Type 2 Respiratory Failure at Adam Malik General Hospital - Lia Mutia Annisa; Fajrinur Syarani; Andika Pradana; Erna Mutiara (Folia Medica Indonesiana)
Highlights: 1. This study provides a comprehensive analysis of various factors such as age, sex, education, occupation, BMI, and comorbidities, and their relationship with bacterial infections in COPD patients experiencing exacerbation and type 2 respiratory failure. 2. While the COPD patients experiencing exacerbation did not exhibit resistance to linezolid and vancomycin, they demonstrated specific antibiotic resistance patterns characterized by high resistance rates to commonly used antibiotics such as meropenem and amikacin. 3. The findings enhance the understanding of the complex interplay of factors influencing infection patterns in this patient population.